The Constitutional Power Of The Executive in The Age of Rule of Law: A Comparative Study on Malaysia and Indonesia - Norazlina binti Abdul Aziz; Rosa Ristawati (Fakultas Hukum, Universitas Warmadewa, 2020)
The rule of law sets as an important principle entrenched in the Constitution of Malaysia and Indonesia. This principle stand as a guardian against abuse of power by the government as nobody shall be above the law. This paper examines the practices of the executive power relating to decision-making policy, execution of power and enforcement activities in Malaysia and Indonesia. It also analyses how the executive branch perfoms the powers in accordance to the rule of law. It mainly focuses on the institutional framework of the head of the government and head of state. The analysis allows for identifications of issues and proposals on the enhancement of the executive branch in both countries that would increase the quality of state administration as well as promoting the rule of law. The study adopts a normative method where the fundamental discussions are based on normative approach with content analysis approach on the constitutional and legal provisions, legal cases, circular and directive. The data acquired through doctrinal study is supported by semi-structured interviews with respondents that have been selected through purposive approach. This article concludes that the executive branch plays important roles in promoting the rule of law in both countries. The Constitution, in this case, provides constitutional limitation for the institutional branch of the executive to perform its powers. In the age of rule of law, the executive powers has to be limited. There is no power without limits. The laws has to provide a clear legal direction and reliable mechanism of checks and balances to govern the exercise of the executive powers.